Forming consumer loyalty of scientific and technical information: the results of a study - A. N. Timokhovich; E. V. Samokhodkin; A. A. Elzon (Вестник университета, 2023)
The article presents the results of a comprehensive study aimed at identifying the features of forming the consumers’ loyalty of scientific and technical information. The scientific work is based on data collected through in-depth interviews among employees of the Department of Long-term Planning and Marketing Research of the All-Russian Institute of Scientific and Technical Information of the Russian Academy of Sciences, as well as analysis of registration questionnaires of clients used to access scientific and technical information. The existing strategies and practices of forming customer loyalty are considered in the context of ensuring effective access to scientific and technical information. The authors identify a number of key principles of work on the formation of consumer loyalty, based on the results of the study: the principle of transparency and trust; the principle of relevance; the principle of accessibility; the principle of personalization; the principle of interaction and feedback. The article presents various aspects affecting the formation of consumer loyalty. Attention is focused on such aspects as the quality of information, its relevance, accessibility and usability. Based on the identified aspects and their impact on the formation of loyalty, the authors have developed recommendations for improving strategies and practices of loyalty formation. The recommendations are intended for organizations generating and distributing scientific and technical information, aimed at strengthening their competitiveness in the information services market. The article identifies potential areas for further research, including a deeper analysis of the needs of specific categories of consumers, as well as the development of specialized methods for forming and maintaining the loyalty of various user groups.